Low dose regimen and formulation of a 5-methyl-1,2,4-oxadiazol-3-yl compound - KIELBASA, William Brian; MERGOTT, Dustin James (2023)
The present invention provides a compound of Formula I:, or a pharmaceutically acceptable salt thereof, wherein the compound of Formula I, or pharmaceutically acceptable salt thereof is administered orally with a total dose of the compound of 0.1 mg/day to 5 mg/day, useful for treating a neurodegenerative disease, including neurodengenerative tauopathies, such as Alzheimers disease, frontotemporal dementia, corticobasilar syndrome, and progressive supranuclear palsy.